Selective Lignin Extraction from Oil Palm Biomass Using Pyridinium Based Protic Ionic Liquids - RASHID, TAZIEN (2018)
Lignin from industrial crops is a renewable biopolymer which can be used for a variety of value-added products. However selective separation of lignin from lignocellulosic biomass is still a current challenge. Existing separation techniques for lignin seperation poses considerable disadvantages such as being energy intensive and environmentally harmful.